Pembentukan Spiritualistas dan Karakter Anak dalam Perspektif Lukman al-Hakim - Hasyim Asyari (Sekolah Tinggi Agama Islam An-Nawawi Purworejo, 2020)
Parents are the first educators for children. The main role of parents is to shape the spirituality and character of children from an early age. Children are taught knowledge about religion and morals through daily activities. The provision of knowledge of religious education from childhood is expected to be able to instill the character and transfer of children. Learning from Lukman Hakim narrated in the Qur'an. Lukman Hakim explicitly educated his children by giving a will related to Islamic education. And Lukman Hakim has a role in giving messages to shape spirituality and character in children. Child's spirituality is reflected by the unity of God to God, carrying out the command of prayer and advice that all actions will be rewarded. While the formation of express characters in Filial discussions to parents, advocates good deeds and prohibits bad deeds, patience, not arrogant, simple life, and polite speaking.